(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The provision of electric power is necessary for the advancement of the country’s economy. It is the main engine of the economy and its various activities. It is an indicator of social welfare and it is considered as the basic pillars for achieving sustainable development (economic, social, environmental and institutional) by raising the levels of performance and meeting local needs. The problem of research was the absence of a program to audit the performance of the electricity sector contributes to ensure the application of sustainable development. The research was based on the hypothesis that the preparation of a proposed program to audit the performance of the electricity sector contributes to the achievement of The researchers sought to employ indicators of sustainable development in auditing the performance of the electricity sector as well as the performance audit indicators issued by the Federal Audit Bureau in accordance with the dimensions of sustainable development, through the preparation of a model "proposed to audit the performance of the electricity sector to achieve sustainable development, To a set of conclusions, the most important of which is the absence of a performance audit program of public electricity institutions that contributes to ensuring the achievement of sustainable development. The study came out with a set of recommendations, the most important of which is the need for an audit program that includes auditing the performance of public electricity institutions ensuring the achievement of sustainable development, for the purpose of promoting the reality of electricity activity to serve current and future generations. of the activity of electricity to serve the current and future generations.